Uneven Use of Remote Work to Prevent the Spread of COVID-19 in South Korea's Stratified Labor Market - Park, Saejung; Lee, Sanghee; Cho, Joonmo (Frontiers in Public Health, 2021)
Background: This research analyzed South Korean companies’ adoption of remote work during the COVID-19 pandemic by focusing on the dual labor market structure comprising of primary sector (large corporations) and secondary sector (small and medium enterprises (SMEs)). Companies in the dual labor market were classified based on firm size. Methods: We used Statistics Korea’s August supplementary data from the Economically Active Population Survey covering 2017–2020. In this empirical study, a Linear Probability Model was used to analyze the probability that employees would work for companies that introduced remote work since COVID-19 depending on the size of the company. Results: This study showed three main results. First, unlike other flexible work systems, the use of remote work has increased rapidly since COVID-19. Second, the larger the size of the company, the higher the probability that employees would work for companies that introduced remote work after COVID-19. Third, according to the analysis by industry, the difference in remote work utilization between large corporations and SMEs was relatively small because of a similar working method in manufacturing. Conclusion: Results of this study suggested that polarization within the dual labor market structure also spilled over to companies’ adoption of remote work, which was initially introduced to prevent the spread of the pandemic. This study examined the system and factors of labor-management relations contributing to such polarization and presented policy directions for the current labor market structure.